DNA-PKcs, a novel functional target of acriflavine, mediates acriflavine's p53-dependent synergistic anti-tumor efficiency with melphalan. Issue 1 (1st December 2016) - Cao, Ji; Lin, Guanyu; Gong, Yanling; Pan, Peichen; Ma, Yaxi; Huang, Ping; Ying, Meidan; Hou, Tingjun; He, Qiaojun; Yang, Bo
Abstract: Acriflavine (ACF), a known antibacterial drug, has recently been recognized as a suitable candidate for cancer chemotherapy. However, the molecular target of ACF is not fully understood, which limits its application in cancer therapy. In this study, we established a structure-specific probe-based pull-down approach to comprehensively profile the potential target of ACF, and we identified DNA dependent protein kinase catalytic subunit (DNA-PKcs) as the direct target of ACF. Since DNA-PKcs facilitates the repair process following DNA double-strand breaks, we further developed a drug combination strategy that combined ACF with the bifunctional alkylating agent melphalan, which exerted a p53-dependent synergistic efficacy against human cancer cells both in vitro and in vivo . With these findings, our study demonstrated that structure-specific probe-based pull-down approaches can be used to identify new functional target of drug, and provided novel opportunities for the development of ACF-based antitumor chemotherapies. Highlights: Acriflavine directly binds to DNA-PKcs and inhibits its kinase activity particularly. Acriflavine enhances the DNA damage caused by melphalan and exerts synergistic efficacy with melphalan against cancer cells. The p53 status dictated the cell fate in response to the combination therapy.